2019
DOI: 10.1021/acs.energyfuels.9b00638
|View full text |Cite
|
Sign up to set email alerts
|

Macro- and Microscopic Studies of “Smart Water” Flooding in Carbonate Rocks: An Image-Based Wettability Examination

Abstract: To date, numerous studies have shown that “smart water” flooding can enhance the oil recovery of carbonate reservoirs by altering the rock wettability. In particular, the Ca2+, Mg2+, and SO4 2– ions in smart water play important roles in altering the wettability of carbonate rocks, although their symbiotic effects are still under debate. In this study, we employ both macro- and microscopic methods, including ζ-potential measurements, contact angle measurements, and micro X-ray computed tomography (μ-CT) scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 47 publications
3
13
0
Order By: Relevance
“…Therefore, seawater brine with low Mg 2+ and high SO 4 2– concentration would trigger high repulsive interaction energy and hence alter carbonate rock wettability toward water wetness. The observation herein was consistent to contact angle measurements performed by Ding et al 100 using the same brine composition. Ding et al 100 observed that a decrease in Mg 2+ concentration impacted the wettability alteration process that an increase in SO 4 2– concentration.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Therefore, seawater brine with low Mg 2+ and high SO 4 2– concentration would trigger high repulsive interaction energy and hence alter carbonate rock wettability toward water wetness. The observation herein was consistent to contact angle measurements performed by Ding et al 100 using the same brine composition. Ding et al 100 observed that a decrease in Mg 2+ concentration impacted the wettability alteration process that an increase in SO 4 2– concentration.…”
Section: Resultssupporting
confidence: 92%
“…The observation herein was consistent to contact angle measurements performed by Ding et al 100 using the same brine composition. Ding et al 100 observed that a decrease in Mg 2+ concentration impacted the wettability alteration process that an increase in SO 4 2– concentration. SW0.25Mg resulted in the contact angle of 85.3° as compared to the SW4S measuring contact angle of 98.6°.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…[ 1–10 ] The modification of the ionic composition of water can be examined by reducing the salinity of the injected water, reducing some monovalent ions such as Na + and Cl − , or increasing some divalent ions such as SO 4 2− Ca 2+ and Mg 2+ . [ 11–15 ] These modifications can enhance oil recovery by changing fluid/fluid and fluid/rock interactions. In general, wettability alteration, fine migration, double layer expansion, and reduction of interfacial tension (IFT) are known as the most prominent mechanisms.…”
Section: Introductionmentioning
confidence: 99%